Part of Speech Classification by EFL Students’: A Review about their Familiarity - Asdar Asdar; Hustiana Hustiana; Ahyadi Ahyadi (Hasanuddin University, 2023)
This study is the reflection of part of speech classification by EFL students. This study intended to deduce the students’ familiarity of parts of speech in the EFL Context. The study was accomplished in Universitas Sulawesi Barat, Faculty of Teacher Training and Education, English education department in the academic year 2023-2024. The sample was 97 students of the third semester in English Education department who will begin intermediate grammar class. The instruments used to collect data were tests that contained two types. The first test was the students chose the part of speech of 24 words while the second test was the students answered 14 multiple choices. The result of this study revealed that students‘familiarity about part of speech was still fair. This was evidenced by the data that has been analyzed that the percentage of students who categorized words into the correct part of speech only reached an average of 40%. Besides, the results of multiple choices showed that the most comprehended part of speech was pronoun. It was around 21.6% - 22.7% of the errors found in the students‘ answers and the least comprehended part of speech was adverb and preposition that reached the correct answer around 25.8 %– 29.9%. Thus, it was suggested that the students should learn more about parts of speech. The lecturer must pair the topics taught in class with part of speech so that students became familiar with it and can ultimately differentiate.